2005
DOI: 10.1088/0953-8984/17/15/021
|View full text |Cite
|
Sign up to set email alerts
|

The structure, phase transition and molecular dynamics of [C(NH2)3]3[Sb2Br9]

Abstract: The crystal structures of [C(NH 2 ) 3 ] 3 [Sb 2 Br 9 ] (Gu 3 Sb 2 Br 9 ) at 300 K and of [C(NH 2 ) 3 ] 3 [Sb 2 Cl 9 ] (Gu 3 Sb 2 Cl 9 ) at 90 and 300 K are determined. The compounds crystallize in the monoclinic space group: C2/c. The structure is composed of Sb 2 X 3− 9 (X = Cl, Br) ions, which form two-dimensional layers through the crystal, and guanidinium cations. In Gu 3 Sb 2 Br 9 the structural phase transformation of the first-order type is detected at 435/450 K (on cooling/heating) by the DSC and dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…[57] Several hybrid A 3 M 2 X 9 compounds (A = organic monocation; M = trivalent metal ions and X = halides) of the main group elements have been studied previously,i ncluding MA 3 Sb 2 X 9 (X = Br or I), [58,59] [C(NH 2 ) 3 ] 3 M 2 I 9 (M = Sb or Bi), [60] MA 3 Bi 2 X 9 (X = Br or I). [61] Some of these hybrids adopt A 3 M 2 X 9 -type layered structures [62,63] of the type shown in Figure 1, while others contain dimeric M 2 X 9…”
Section: Methodsmentioning
confidence: 99%
“…[57] Several hybrid A 3 M 2 X 9 compounds (A = organic monocation; M = trivalent metal ions and X = halides) of the main group elements have been studied previously,i ncluding MA 3 Sb 2 X 9 (X = Br or I), [58,59] [C(NH 2 ) 3 ] 3 M 2 I 9 (M = Sb or Bi), [60] MA 3 Bi 2 X 9 (X = Br or I). [61] Some of these hybrids adopt A 3 M 2 X 9 -type layered structures [62,63] of the type shown in Figure 1, while others contain dimeric M 2 X 9…”
Section: Methodsmentioning
confidence: 99%
“…[57] Several hybrid A 3 M 2 X 9 compounds (A = organic monocation; M = trivalent metal ions and X = halides) of the main group elements have been studied previously,i ncluding MA 3 Sb 2 X 9 (X = Br or I), [58,59] [C(NH 2 ) 3 ] 3 M 2 I 9 (M = Sb or Bi), [60] MA 3 Bi 2 X 9 (X = Br or I). [61] Some of these hybrids adopt A 3 M 2 X 9 -type layered structures [62,63] of the type shown in Figure 1, while others contain dimeric M 2 X 9 3À anions comprising two face-sharing MX 6 octahedra.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The C7 atom is split between two positions with occupancy factors of 0.64 for C7 and 0.36 for C7A. The same type of disorder for the nbutylammonium cation was found in the structure of (n-C 4 H 9 NH 3 ) 2 [BiCl 5 ] [11]. It is suggested that the ethyl group of the alkylammonium chain undergoes a reorientation around the C5-C7 bond [11].…”
Section: Structure At 260 Kmentioning
confidence: 70%
“…The lone electron pair may be easily deformed from the initial symmetry as a result of a formation of M-X-M (M = Bi, or Sb; X = Cl, Br or I) bonds. When two octahedra are joined together having common (X) halogen atoms the bridging M-X bond length is increased, whereas the oppo- 3 Cl 9 ], where in the octahedral configuration of the antimony atom there are three bridging Sb-Cl bonds, the length of which is 2.915(10)Å, whereas the three terminal ones, have a length of 2.446(1)Å [11]. It should be noted that the increase of bond lengths compared to not deformed octahedron in this case is 0.27Å, whereas the decrease in length of the opposite bonds is 0.20Å.…”
Section: Introductionmentioning
confidence: 99%